PELAYANAN PERIZINAN KABUPATEN PONOROGO - Rahmawati, Alfiyatur (Faculty of Social and Political Science Universitas Brawijaya, 2017)
The low quality of public services in the field of licensing causes the community and businesses reluctant to take care licensing. The low quality of licensing service is demonstrated by the absence of a mechanism or procedure clearly regulating the licensing, long processing time, costs and conditions of licensing. Ponorogo Regency government respond to central government policies that aim to improve and simplify system of licensing services with the establishment of the Integrated Licensing services Office (KPPT) in 2009. This is a manifestation of a serious commitment under the leadership of the Regent of Ponorogo, Muhadi Suyono, to improve continuously the image of public services in order to be better in the future. Ponorogo KPPT continues to make improvements in terms of improved public services, opens to the public comments and suggestions regarding the performance KPPT, and accesses clear information to the applicant to take care of all licensing. The main change resulted with improvement in field of licensing in Ponorogo is the openness of the clear procedures to manage licensing, range time to take care every kinds of licensing respectively, the requirement to be met, the costs and reduce the practice of widespread extortion by officers.